2019
DOI: 10.2147/ndt.s226353
|View full text |Cite
|
Sign up to set email alerts
|

<p>Meta-Analysis of Clipping versus Coiling for the Treatment of Unruptured Middle Cerebral Artery Aneurysms: Direct Comparison of Procedure-Related Complications</p>

Abstract: BackgroundEndovascular coiling and surgical clipping are routinely used to treat unruptured middle cerebral artery aneurysms (MCAAs). However, the optimal treatment for unruptured MCAAs is controversial. We aimed to systematically and comprehensively compare the clinical outcomes between endovascular coiling and surgical clipping for the treatment of MCAAs.MethodThis meta-analysis retrieved academic articles comparing the clinical outcomes between endovascular coiling and surgical clipping for unruptured MCAAs… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
12
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 13 publications
(13 citation statements)
references
References 28 publications
1
12
0
Order By: Relevance
“…The systematic review and meta-analysis of the literature was performed based on the Preferred Reporting Items for Systematic Reviews and Meta-Analyses (PRISMA) ( 12 ).…”
Section: Methodsmentioning
confidence: 99%
“…The systematic review and meta-analysis of the literature was performed based on the Preferred Reporting Items for Systematic Reviews and Meta-Analyses (PRISMA) ( 12 ).…”
Section: Methodsmentioning
confidence: 99%
“…For MCA aneurysms, several studies showed that the efficacy of the surgical clipping is better than the coiling with regard to the occlusion rate. 4 5 6 7 16 However, with regard to the functional outcome and procedural complications, the endovascular approach was comparable to the surgical clipping. 5 7 MCAB aneurysms typically have a wide neck that usually incorporates the origin of one or both M2 branches.…”
Section: Discussionmentioning
confidence: 94%
“…Surgical clipping still represents the gold standard for treatment of MCA aneurysms in all experienced tertiary referral cerebrovascular centers, since several studies have supported the superiority of open surgery in obtaining complete aneurysm occlusion with distal flow preservation and lower risk of thromboembolism of the perforators and hemorrhagic infarction. 12 Moreover, a lower risk of long-term recurrence and a reduced probability of retreatment have also been associated with surgical clipping compared with coiling. 13…”
Section: Discussionmentioning
confidence: 99%